2015
DOI: 10.1094/cchem-01-15-0017-r
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Perennial Wheatgrass (Thinopyrum intermedium) and Refined Wheat Flour Blends: Impact on Rheological Properties

Abstract: Cereal Chem. 92(5):434-440Intermediate wheatgrass (IWG) (Thinopyrum intermedium) is a perennial grass with desirable agronomic traits and positive effects on the environment. It has high fiber and protein contents, which increase the interest in using IWG for human consumption. In this study, IWG flour was blended with refined wheat at four IWG-to-wheat ratios (0:100, 50:50, 75:25, and 100:0). Samples were analyzed for proximate composition, microstructure features, pasting properties (Micro Visco-Amylo-Graph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
66
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 38 publications
9
66
4
Order By: Relevance
“…Compared to wheat, IWG is generally higher in protein, fiber and antioxidants, but lower in total starch [2]. While higher in protein content, we found that the protein distribution/profile of IWG is considerably different than that of common wheat.…”
contrasting
confidence: 61%
“…Compared to wheat, IWG is generally higher in protein, fiber and antioxidants, but lower in total starch [2]. While higher in protein content, we found that the protein distribution/profile of IWG is considerably different than that of common wheat.…”
contrasting
confidence: 61%
“…Gluten aggregation was also assessed on a GlutoPeak (C. W. Brabender Instruments, South Hackensack, NJ, USA) following the procedure reported by Marti et al . (). Pasting profile was evaluated followed the method outlined by Marti et al .…”
Section: Methodsmentioning
confidence: 97%
“…Pasting profile was evaluated followed the method outlined by Marti et al . () using a Micro‐Viscoamylograph (C. W. Brabender Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…By analyzing gluten aggregation behaviors of 19 winter wheat cultivars, Marti et al (2015a) found that T max was related to gliadin or SDS-soluble protein, whereas PT and PA were significantly associated with concentrations of glutenin macropolymer. durum) (Quayson et al 2016) and blended flours with addition of functional ingredients such as perennial wheat grass (Marti et al 2015b), kamut and millet flours (Chandi et al 2015), intermediate wheat grass flour (Thinopyrum intermedium) , and wheat germ (Marti et al 2014b). durum) (Quayson et al 2016) and blended flours with addition of functional ingredients such as perennial wheat grass (Marti et al 2015b), kamut and millet flours (Chandi et al 2015), intermediate wheat grass flour (Thinopyrum intermedium) , and wheat germ (Marti et al 2014b).…”
mentioning
confidence: 99%